Shifting Paradigm of Modern Islam Fundamentalism as Islamized Space Autonomy in Indonesia - Ariwidodo, Eko (Institut Agama Islam Negeri Madura, 2017)
Idealism various groups of political Islam failed to change the political landscape of the Middle East and some other regions. Political Islam is not won power, while the old regimes are still in power. Western powers are increasingly plugging hegemony (political, economic, cultural) in the region. Political Islam is also not always successfully display the values contained in the ideals of fundamentalism in the form of the application of religious laws in politics. Islamic fundamentalists in some places only produce changes that are not significant in the fields of law, politics and economics. In this case, fundamentalism does emphasize the application of Sharia totally, but often do not care about the character of the political system. The variant of the traditional and modern fundamentalism fundamentalism can be seen also shift to the neo-fundamentalism. Orientation and strategy of neo-fundamentalism is the master of society through social action, far from being revolutionary, neo-fundamentalists are now entering into civil society and political classes. Although the character of the revolution is lost, the symbols of Islam seeped into the public and political discourse of Islam. Neo-fundamentalism seeks re-islamization society at grassroots level, and no longer through the country. Fundamentalists are directing the struggle in the birth of an Islamic society and Islamic space. This shift has seen as a symbol of Islamic fundamentalism in the political failure that resulted in a significant change in the weight of thought and movement.Copyright (c) 2017 by KARSA. All right reservedÂ DOI: 10.19105/karsa.v25i1.1357